When ladies meet [videorecording (DVD)] - Leonard, Robert Z., 1889-1968; Leonard, Robert Z., 1889-1968; Crawford, Joan, 1908-1977; Taylor, Robert, 1911-1969; Garson, Greer, 1904-1996; Marshall, Herbert, 1890-1966; Byington, Spring, 1886-1971; Crothers, Rachel, 1878-1958 (Distributed by Warner Home Video, 2009)
Joan Crawford plays an author who falls in love with her married publisher in this excellent drama, which keeps flowing at a brisk pace thanks to a good dose of sly, comedic overtones.